Evaluasi Sistem Akuntansi Penerimaan Dan Pengeluaran Kas Terhadap Pengendalian Piutang Dan Hutang Pada PT. Fortunindo Artha Perkasa - Magdalena, Annaria; Marlina, Tri; Amelia, Siska (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
The purpose of this study was to evaluate the role of accounting system of cash receipts to receivable and liability controling in company operating activity. This evaluation was completed to identifi the advantages and disadvantages of acoounting system of cash flow of a company. This study was conducted in PT. Fortunindo Artha Perkasa at Jl. Raya Segitiga Puncak, Sukabumi Bogor, Pasar Ciawi. PT. Fortunindo Artha Perkasa is a company spesializes in corporate real estate, including building sale, and purchase with its land rights, managing and leasing buildings, oficces, shops and markets, parkings, and warehousings. The result identified that there is a shortage of accounting system applied manually, so that all forms of division of tasks and functions within the company should be run more effectively in order to avoid errors in recording and reporting. To overcome this company should be described in the form ofa flowchart so visible automatically, quickly, and integrated into the entire operations of the company, where the performance of existing business processes in the company are described using the flowchart. Keywords : cash receipt, receivable and liability controlling, manual accounting system